1997
DOI: 10.1097/00002030-199714000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Change in sexual behaviour and decline in HIV infection among young pregnant women in urban Uganda

Abstract: This is the first report of a change over a period of 6 years in male and female sexual behaviour, assessed at the population level, that may partly explain the observed decline in HIV seroprevalence in young pregnant women in urban Uganda. This result should encourage AIDS control programmes to pursue their prevention activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
105
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(110 citation statements)
references
References 12 publications
5
105
0
Order By: Relevance
“…These means are estimated from Ugandan data for the number of heterosexual partners in the past year (33) and the number of nonregular heterosexual partners (i.e., spouses or long-term partners) in the past year (34). In these sexual activity surveys, men invariably have more new partnerships; thus, we assumed that they would have fewer average contacts per partnership than women (a higher rate of new partner acquisition means fewer sexual contacts with a given partner; ref.…”
Section: The Modelmentioning
confidence: 99%
“…These means are estimated from Ugandan data for the number of heterosexual partners in the past year (33) and the number of nonregular heterosexual partners (i.e., spouses or long-term partners) in the past year (34). In these sexual activity surveys, men invariably have more new partnerships; thus, we assumed that they would have fewer average contacts per partnership than women (a higher rate of new partner acquisition means fewer sexual contacts with a given partner; ref.…”
Section: The Modelmentioning
confidence: 99%
“…Indeed, in Uganda in the 1990s, the rapid increase in age at first sex in urban areas was considered to be an important contributing factor in the decline of HIV prevalence. 2 For such reasons, initiatives to delay sexual debut have been considered as a potentially important component of HIV prevention programmes in sub-Saharan Africa. 3 However, although girls' early sexual debut has been posited as an important risk factor for HIV infection, the mechanisms through which this increased risk may occur have not been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…The respondents often mentioned quick progress of the disease and dying faster as effect of one knowing his/her sero status which may be an expressed form of fear of positive results. It has been shown that fear of positive HIV results may be a barrier to HIV testing (17)(18)(19)(20)(21). Similarly as expected late testing was favoured by having an illness in the last two months suggesting that HIV/AIDS related or similar symptoms may actually influence the decision to undertake a test (16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 84%